The supervised internship in the university formation as construction of the professional teaching base for the formation of literary readers - Oliveira, Célia Zeri de (Revista Hipótese, 2021)
This article intends to do a contribution to the formation of literary readers through the discussion about the purposes of literature as art, and, in this conception, as a way of humanizing of human beings by the principle of otherness. The researches in the area of teacher education has demonstrated the advances achieved in relation to the teaching of literature in the schooling process of basic education and relate, through the case study, the realization of the skills for the training of readers for a specific pupils, students of a Quilombola School.
Keywords: Readers’ formation; Supervised internship; Literary reading